Measuring The Effectiveness of University Programmes Based on Evaluation Models: A Meta-Analysis - Manap, R.; Othman, N.; Roslan, S.N.; Ismail, K.; Kamarubahrin, A.F. (Universiti Sains Islam Malaysia, 2024)
This article presents an extensive systematic review and meta-analysis on the effectiveness of university programmes based on different evaluation models. This study was conducted on primary sources published between year 2000 to 2018 using systematic searches from online databases including EBSCOhost, CENGAGE Learning, Cochrane Library, Clinical Key, ProQuest, ScienceDirect, and Scopus. There were, twenty-eight studies found on measuring the effectiveness of university programmes using different evaluation models. From these studies, the most common evaluation models used are the Context Input Process Product (CIPP) model and the Kirkpatrick model. It is concluded that the effectiveness of a programme needs to be improved through the implementation of optimising training designs, redefining training roles, management commitment, attention to individual and use of ongoing evaluation.